Influence of the Boy Band BTS As Brand Ambassadors To Purchase Intention Mediated by Tokopedia 's Brand Image and Brand Awareness in Indonesia - Dian Saputri, Silvi; Vandayuli Riorini, Sri; Badzlina Nabila, Lintang (Riviera Publishing, 2023)
BTS is currently the most famous Korean idol boy band not only in Indonesia but also throughout the world. Because of their high profits, many large companies are eyeing to work with them as Brand Ambassadors and product influencers, eventually giving rise to the term